Cote d'Ivoire : 2007 Article IV Consultation and Request for Emergency Post-Conflict Assistance-Staff Report; Staff Statement; Staff Supplement; Public Information Notice and Press Release on the Executive Board Discussion;. (IMF Staff Country Reports; Country Report ;, 2007)
This 2007 Article IV Consultation highlights that Cote d'Ivoire's crisis has taken a heavy toll on growth and social conditions. Per capita income fell by one-sixth, poverty rose, and many social indicators worsened. These developments have also hurt regional trade and output. The external current account has remained in surplus, helped by resilient cocoa production and favorable prices. The outlook for 2007 is for a modest recovery to 1 1\2 percent output growth, depending on progress in political normalization and the restoration of public services throughout the country.